Pulmonary arterial hypertension associated with systemic sclerosis in the Czech Republic - Jansa, Pavel; Becvar, Radim; Ambroz, David; Palecek, Tomas; Tomcik, Michal; Skacelova, Simona; Aschermann, Michael; Linhart, Ales (Clinical rheumatology, 2012)
BACKGROUND: Systemic sclerosis (SSc) is an important cause of pulmonary arterial hypertension (PAH), with an estimated prevalence of 7.85-26.7%. OBJECTIVE: Our aim was to estimate the prevalence of PAH among patients with SSc in the Czech Republic and to compare haemodynamics in SSc patients diagnosed with PAH through screening with those diagnosed previously, based on symptoms. METHODS: During 2007, SSc patients in the Czech Republic, without significant pulmonary function impairment or cardiac disease, underwent screening for PAH with transthoracic echocardiography. Those with a tricuspid regurgitant (TR) jet gradient suggestive of PAH (>30 mmHg) underwent subsequent right heart catheterisation (RHC) to confirm the diagnosis (mean pulmonary arterial pressure, mPAP, ≥25 mmHg; pulmonary capillary wedge pressure, ≤15 mmHg). Haemodynamics in patients diagnosed with PAH in this way were compared with those in patients diagnosed previously, based on symptoms. RESULTS: Two hundred and three SSc patients (mean age, 53.8 ± 13 years; 82.3% women) from 26 rheumatology practices were screened. Among these, 17 had a TR jet gradient >30 mmHg and underwent RHC; PAH was confirmed in six patients. These six patients were found to have significantly lower mPAP than nine patients diagnosed previously with PAH, based on symptoms (31.17 ± 5.56 vs. 46.89 ± 9.48 mmHg, p = 0.0014). CONCLUSION: Prevalence of PAH in our SSc cohort was 7.08%. SSc patients diagnosed with PAH through screening have less advanced disease in terms of haemodynamics than those with PAH diagnosed previously based on symptoms; their prognosis is therefore likely to be more favourable.
Keywords: respirační funkční testy; Comorbidity; Male; kohortové studie; arteria pulmonalis; Cohort Studies; plíce; Pulmonary Artery; Česká republika; systémová sklerodermie; Adult; prevalence; Hypertension, Pulmonary; Aged; dospělí; mužské pohlaví; senioři; komorbidita; Lung; Czech Republic; lidé; ženské pohlaví; Humans; Respiratory Function Tests; Prevalence; Female; plicní hypertenze; lidé středního věku; Scleroderma, Systemic; Middle Aged